2022
DOI: 10.1200/op.21.00683
|View full text |Cite
|
Sign up to set email alerts
|

Financial Hardship in Patients With Head and Neck Cancer

Abstract: PURPOSE: Financial hardship is a growing concern for patients with cancer. Patients with head and neck cancer (HNC) are particularly vulnerable, given that a third leave the workforce following treatment. The goal of our study was to characterize financial hardship in the psychologic response (response to increased expenses) and coping behaviors (behaviors patients adopt to manage their care in the setting of increased expenses) domains in patients with HNC compared with patients with other cancers. METHODS: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 24 publications
0
23
1
Order By: Relevance
“…Less than half (46%) of HNC patients agreed to participate in this study and provide information on the extent of financial toxicity they experienced. Compared to other financial toxicity studies among the HNC population, 9 , 10 , 12 , 13 , 14 , 39 , 40 we observed lower consent rates. This may be, in part, due to the ongoing coronavirus pandemic.…”
Section: Discussioncontrasting
confidence: 92%
“…Less than half (46%) of HNC patients agreed to participate in this study and provide information on the extent of financial toxicity they experienced. Compared to other financial toxicity studies among the HNC population, 9 , 10 , 12 , 13 , 14 , 39 , 40 we observed lower consent rates. This may be, in part, due to the ongoing coronavirus pandemic.…”
Section: Discussioncontrasting
confidence: 92%
“…Prospective or combined retrospective and prospective data collection was conducted in 6 cases 7 , 21 , 22 , 30 , 32 , 36 . Two retrospective studies were multicentric 18 , 23 , whereas six articles analysed financial data from national databases 19 , 20 , 25 , 27 , 28 , 33 .…”
Section: Resultsmentioning
confidence: 99%
“…We found health outcomes to address function and quality of life, rather than costs, health care utilization and mortality. Studies are needed that investigate and intervene on cost and financial toxicity, a recognized concern for HNC patients that are particularly vulnerable given the high rate of workforce exit 4 , 5 and gaps in dental coverage. 49 Due to the high prevalence of chronic medical conditions, subsequent cancers, smoking and other symptoms specific to HNC survivors, hospitalization and emergency‐department utilization, and mortality are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Psychosocial effects are also significant, with HNC survivors experiencing high rates of depression and suicide, 3 fear of cancer recurrence, 3 and financial toxicity. [4][5][6][7] Both recurrence and subsequent malignancies are common, especially among HNC survivors with heavy alcohol and tobacco use. 8 Furthermore, HNC survivors may have pre-existing comorbidities that require ongoing medical management and health promotion to reduce risk.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation